PERKEMBANGAN DAN PERAN OPAC PADA APLIKASI CIP (CERAH INFORMASI PUSTAKA) UNTUK TEMU KEMBALI INFORMASI DI PERPUSTAKAAN UNIVERSITAS TRIDINANTI PALEMBANG - Elsadantia, Betari Ayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
In my research, this article will discuss the development and role of OPAC in the CIP (Sunny Information Library) application for retrieval of information in the Palembang Tridinanti Library. This article will discuss the development and role of OPAC in the CIP (Sunny Information Library) application in improving Palembang Tridinanti Library services, as well as the effectiveness of the development and role of OPAC in CIP (Sunny Information Library) as a information retrieval system in the library. In the era of globalization 4.0, information technology-based libraries are expected to be able to provide convenience for users and provide information that is faster and more precise. The research method used in completing this article is to use qualitative research methods with interview and observation data collection techniques. Interview, is a series of steps required in conducting qualitative interviews. Meanwhile, observation is an important tool for collecting data in qualitative research. These observations are based on the research objectives and research statements. The results of this study indicate that the development and application of OPAC in the CIP (Sunny Information Library) application in improving library services at the Palembang Tridinanti Library in accessing information regarding the availability of documents, library materials, and data in the library quickly and accurately. The effectiveness of the development and role of the OPAC in the CIP (Sunny Information Library) application for users has been used by some users to facilitate searches carried out inside and outside the library because the OPAC in the CIP application (Sunny Information Library) itself is web-based, that is, it can be accessed when the device we are connected to the internet network.